Long noncoding RNA XIST knockdown relieves the injury of microglia cells after spinal cord injury by sponging miR-219-5p - Zhong Xueren (De Gruyter, 2021)
Long noncoding RNAs have been demonstrated to play crucial roles in the pathogenesis of spinal cord injury (SCI). In this study, we aimed to explore the roles and underlying mechanisms of lncRNA X-inactive specific transcript (XIST) in SCI progression. SCI mice model was constructed and evaluated by the Basso–Beattie–Bresnahan method. The SCI cell model was constructed by treating BV2 cells with lipopolysaccharide (LPS). The levels of XIST and miR-219-5p were determined by the reverse transcription quantitative polymerase chain reaction. The concentrations of inflammatory cytokines were measured by enzyme-linked immunosorbent assay. Protein levels were measured via western blot assay. Cell viability and apoptosis were evaluated by cell counting kit-8 assay and flow cytometry analysis, respectively. The relationship between XIST and miR-219-5p was analyzed by online tool starBase, dual-luciferase reporter assay, and RNA immunoprecipitation assay. As a result, the XIST level was enhanced and the miR-219-5p level was declined in the SCI mice model. XIST was also upregulated in LPS-induced BV2 cells. LPS treatment restrained BV2 cell viability and accelerated apoptosis and inflammatory response. XIST knockdown effectively weakened LPS-induced BV2 cell injury. miR-219-5p was identified as a target of XIST. Moreover, inhibition of miR-219-5p restored the impacts of XIST knockdown on cell viability, apoptosis, and inflammation in LPS-treated BV2 cells. In addition, LPS-induced XIST promoted the activation of the nuclear factor-κB (NF-κB) pathway by sponging miR-219-5p. In conclusion, XIST silencing promoted microglial cell viability and repressed apoptosis and inflammation by sponging miR-219-5p, thus promoting the recovery of SCI.